Quality of Life in Patients With Rectal Resections and End-to-End Primary Anastomosis Using a Standardized Perioperative Pathway - Herzberg, Jonas; Khadem, Shahram; Begemann, Valentin; Strate, Tim; Honarpisheh, Human; Guraya, Salman Yousuf (Frontiers in Surgery, 2022)
Objectives: Lower rectal resection is associated with a high rate of postoperative complications and, therefore, adversely impacts the postoperative health-related quality of life (QoL). Though sporadically practiced in different centers, there is no standard perioperative protocol for the management of patients with rectal growths. The aim of this analysis is to evaluate the patient-reported outcomes after low rectal resections followed by an end-to-end-reconstruction and temporary covering ileostomy using a multidisciplinary fail-safe-concept. Methods: Between 2015 and 2020, we evaluated patient reported outcomes after open and laparoscopic rectal resections with end-to-end reconstruction with a primary straight anastomosis using a standardized perioperative pathway All patients with stoma were excluded from the study. The data for the QoL of patients was collected using the established Low Anterior Resection Syndrome (LARS) -score and the EORTC-C30 and CR-29 questionnaires at a single postoperative timepoint. Results: We recruited 78 stoma-free patients for this analysis. Of 78 patients included in the study, 87.2 % were operated laparoscopically and the mean global health status was 67.95 points, while a major LARS was detected in 48 (61.5 %) patients. No anastomotic leakage (AL) occurred within the study cohort. There was no significant change in the LARS-score or the global health status depending on the follow-up-period. Conclusion: This study shows that good QoL and functional outcomes with no AL are achievable following end-to-end straight anastomosis using a standardized perioperative surgical fail-safe protocol procedure.